Cohen-Macaulay modules over the plane curve singularity of type T₄₄, II - Drozd, Y.A.; Tovpuha, O.V. (Algebra and Discrete Mathematics, 2019)
We accomplish the classification of Cohen–Macaulay modules over the curve singularities of type T₄₄ and the description of the corresponding matrix factorizations, started in [8].